2012
DOI: 10.1007/s00339-012-6874-x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of GaN light-emitting diodes with surface-treated Al-doped ZnO transparent Ohmic contacts by holographic photonic crystal

Abstract: This letter presents a holographic photonic crystal (H-PhC) Al-doped ZnO (AZO) transparent Ohmic contact layer on p-GaN to increase the light output of GaN-based LEDs without destroying the p-GaN. The operating voltage of the PhC LEDs at 20 mA was almost the same as that of the typical planar AZO LEDs. While the resultant PhC LED devices exhibited significant improvements in light extraction, up to 1.22 times that of planar AZO LEDs without PhC integration. Temperature dependence of the integrated photolumines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…13 Nonetheless, AZO electrodes directly on p-GaN do not give the best performance, with I−V curves showing nonlinear characteristics or high specific contact resistances (ρ c ). 14,15 Hence, different interlayers such as Ni, 16−18 Pt, 12,19 ITO, 20,21 or Ag 12,22 have been used for Ohmic contacts to p-GaN.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Nonetheless, AZO electrodes directly on p-GaN do not give the best performance, with I−V curves showing nonlinear characteristics or high specific contact resistances (ρ c ). 14,15 Hence, different interlayers such as Ni, 16−18 Pt, 12,19 ITO, 20,21 or Ag 12,22 have been used for Ohmic contacts to p-GaN.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Contacts with transparent conductive oxides such as Sn-doped In 2 O 3 (ITO) and Al-doped ZnO (AZO) have been developed, with AZO being more appealing than ITO as it is more environmentally friendly and cheaper, as well as having better electrical and optical properties . Nonetheless, AZO electrodes directly on p-GaN do not give the best performance, with I–V curves showing nonlinear characteristics or high specific contact resistances (ρ c ). , Hence, different interlayers such as Ni, Pt, , ITO, , or Ag , have been used for Ohmic contacts to p-GaN.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difference of the electron affinities between AZO (4.7 eV) and p-GaN (7.5 eV) [15], it is difficult to achieve ohmic contacts by directly depositing AZO onto GaN [16], although it was reported that after annealing the deposited AZO films on p-GaN resulted in ohmic behavior [17, 18]. To solve the problem, several kinds of interlayers have been introduced, e.g., NiO [16], Ag nanoparticles [19, 20], p-InGaN [21], Pt layer [22] and InON nanodots [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, doped zinc oxide (ZnO) has been suggested as an alternative to ITO film for NUV‐LEDs. For instance, Horng et al recently reported highly transparent conductive gallium‐doped ZnO (GZO) film, and Yang et al reported aluminum‐doped ZnO (AZO) film. Ga 2 O 3 film is another alternative to ITO films because Ga 2 O 3 shows a wider bandgap than ITO, so it is more optically transparent and absorbs less UV light than ITO .…”
Section: Introductionmentioning
confidence: 99%